Generating a Dynamic Mesh by Simulation the Behaviour of Deformable Material using a Virtual Mesh - محمد نسرين (Latakia University Journal -Engineering Sciences Series, 2024)
The suitability of a mesh for a dynamic motion of bodies is of paramount importance, where researchers in the field of numerical solutions of flow equations can simulate the movement of bodies underwater in a realistic manner. In this research, a dynamic mesh has been generated by approximating the motion of the finite elements mesh with the behaviour of a deformable material subjected to deformations. The displacement of the moving body at each time step serves as the boundary conditions that cause the finite elements mesh to move without deforming its shape. This method relies on dividing the computational domain into a limited number of finite elements with large geometric dimension, subjecting these elements to displacements and projecting the coordinates of the finite elements within the large elements; after the latter have undergone the displacement. Finally, this approach has contributed efficiently to conserving the quality of the mesh during the body motion.